Engaging Stakeholders In Public Sector Healthcare: Driving Transformation In The Eastern Cape Department Of Health's Re-Engineering Journey - Rasmeni, Ella; Rulashe, Tando; Conradie, Hendrik Francois (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
The Eastern Cape Department of Health (ECDoH) is undergoing a re-engineering process to enhance service efficiency and address organizational inefficiencies, such as a bloated structure and excessive personnel costs. However, employees, as key stakeholders, were not meaningfully engaged in the process. This study investigates the role of stakeholder engagement in the ECDoH's transformative efforts, highlighting its impact on inclusivity, strategic alignment, and transparency. Grounded in a constructivist paradigm, this study adopts a qualitative approach using focus group discussions with 12 participants from diverse stakeholder groups. Thematic analysis revealed critical gaps in the ECDoH's engagement strategy, including the absence of a stakeholder engagement plan and the top-down nature of decision-making, which excluded employees' input. Employees were aware of the re-engineering process but expressed concerns about the lack of transparency and the potential adverse effects, such as demotions and job transfers. The findings emphasize the risks of excluding employees from decision-making, including resistance, litigation, and decreased morale. Recommendations include the development of a comprehensive stakeholder engagement plan that encourages participatory decision-making, promotes transparency, and leverages employees' insights to enhance organizational change processes. This study critically explores the importance of integrating stakeholder engagement into re-engineering initiatives to ensure buy-in, reduce implementation challenges, and achieve sustainable organizational transformation. It contributes to the broader discourse on employee participation in public sector reforms, offering insights for policymakers and organizational leaders.